A thermodynamic approach to the precipitation hardening of magnesium alloy with high formability. (15th March 2023) - Lee, Jong-Kwan; Jang, Hyo-Sun; Zargaran, Alireza; Tapia, Antonio João Seco Ferreira; Kim, Nack Joon; Lee, Byeong-Joo
Abstract: The poor formability of magnesium alloys at room temperature remains an obstacle to their wider application in industry. In a previous study, the present authors' group optimized the composition of a Mg-Zn-Ca alloy, achieving high ductility and formability, using an atomistic simulation, and the alloy showed high ductility and formability but low strength. Since magnesium alloy is a structural material, reasonable strength is required and precipitation hardening can be an effective way to improve strength. Important here is that the alloying added for precipitation hardening should not have a harmful effect on the carefully optimized ductility and formability. A thermodynamic calculation was performed to select the suitable alloying elements for precipitation hardening and to determine their optimum composition. This study suggests a new alloy design technique to improve strength without disturbing the well-optimized ductility and formability, together with experimental verification. Graphical Abstract: Image, graphical abstract